Characterization of Non-Invasively Induced Post-Traumatic Osteoarthritis in Mice - Fazal-; Yong-Hoon Jeong; Do-Gyoon Kim; Ae-Kyung Yi; David D. Brand; Karen A. Hasty; Hongsik Cho (MDPI AG, 2022)
The pathophysiology of post-traumatic arthritis (PTOA) is not fully understood. This study used non-invasive repetitive mechanical loading (ML) mouse models to study biochemical, biomechanical, and pain-related behavioral changes induced in mice. Mouse models reflected the effects of the early stages of PTOA in humans. For the PTOA model, cyclic comprehensive loading (9N) was applied to each mouse's left knee joint. ML-induced biochemical and molecular changes were analyzed after loading completion. Cartilage samples were examined using gene expression analysis. Tissue sections were used in subsequent OA severity scoring. Biomechanical features and pain-related behavior were studied after 24 h and three weeks post-ML sessions to examine the development of PTOA. The loaded left knee joint showed a greater ROS/RNS signal than the right knee, which was not loaded. There was a significant increase in cartilage damage and MMP activity in the mechanically loaded joints relative to non-loaded control knee joints. Similarly, we found a difference in the viscoelastic tangent, which highlights significant changes in mechanical properties. Biochemical analyses revealed significant increases in total NO, caspase-3 activity, H2O2, and PGE2 levels. Gene expression analysis highlighted increased catabolism (MMP-13, IL-1β, TNF-α) with a concomitant decrease in anabolism (ACAN, COL2A1). Histopathology scores clearly indicated increases in OA progression and synovitis. The gait pattern was significantly altered, suggesting signs of joint damage. This study showed that biomechanical, biochemical, and behavioral characteristics of the murine PTOA groups are significantly different from the control group. These results confirm that the current mouse model can be considered for translational PTOA studies.